SOME KEY ISSUES IN AFRICAN TRADITIONAL EDUCATION - Adeyemi, Michael Bamidele; Adeyinka, Augustus Adeleke (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2002)
ABSTRACT. Against a background discussion of the concept and general purpose of education, this article examines sorne key issues in African traditional education, namely its philosophical foundations, content and methods, strengths and weaknesses. The philosophical foundations of African traditional education are the five principles of preparationism, functionalism, communalism, perennialism and holisticism. We have highlighted the physical, social and spiritual content of African traditional education and the practical method of teaching and learning. The strengths and weaknesses of African traditional education are discussed and the attention of readers directed to possible areas for further study. PRINCIPAUX ENJEUX DE L’ÉDUCATION TRADITIONNELLE AFRICAINE RÉSUMÉ. Avec en toile de fond le concept philosophique et le but général de l’éducation, cet article analyse certains des grands enjeux de l’éducation traditionnelle africaine, à savoir: les fondements philosophiques, le contenu et les méthodes, les points forts et les faiblesses. Les fondements philosophiques de l’éducation traditionnelle africaine sont les cinq principes du «préparationnisme», du fonctionnalisme, du communalisme, de la pérennité et de l’holisme. Nous avons mis en lumière le contenu physique, social et spirituel de l’éducation traditionnelle africaine et la méthode pratique et communautaire d’enseignement et d’apprentissage. Les points forts et les faiblesses de l’éducation traditionnelle africaine sont analysés par rapport à la société contemporaine. Nous terminons cet article en attirant l’attention du lecteur sur d’éventuels domaines d’études plus approfondies.